2019
DOI: 10.3390/ijerph16214153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Water Soluble Uremic Toxins and Urinary Acute Kidney Injury Biomarkers After 10- and 100-km Runs

Abstract: Acute kidney injury (AKI) is described as a relatively common complication of exercise. In clinical practice the diagnosis of AKI is based on serum creatinine, the level of which is dependent not only on glomerular filtration rate but also on muscle mass and injury. Therefore, the diagnosis of AKI is overestimated after physical exercise. The aim of this study was to determine changes in uremic toxins: creatinine, urea, uric acid, asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 70 publications
0
32
0
1
Order By: Relevance
“…Bongers, who studied uNGAL after 30 and 150 min of exercise, found that uncorrected uNGAL and uNGAL corrected to osmolality were increased, while there were no changes in uNGAL corrected to creatinine and cystatin-C [26]. After a 10-km run, both uNGAL and uNGAL/Cr increased significantly (3.9-and 2.9-fold, respectively) in the Wołyniec study [45]. Otherwise, in Semen et al's study, a 10 km run caused an increase in uNGAL only when combined with ibuprofen/naproxen use [49].…”
Section: Changes In Ungal After Exercises Shorter Than a Marathonmentioning
confidence: 87%
See 3 more Smart Citations
“…Bongers, who studied uNGAL after 30 and 150 min of exercise, found that uncorrected uNGAL and uNGAL corrected to osmolality were increased, while there were no changes in uNGAL corrected to creatinine and cystatin-C [26]. After a 10-km run, both uNGAL and uNGAL/Cr increased significantly (3.9-and 2.9-fold, respectively) in the Wołyniec study [45]. Otherwise, in Semen et al's study, a 10 km run caused an increase in uNGAL only when combined with ibuprofen/naproxen use [49].…”
Section: Changes In Ungal After Exercises Shorter Than a Marathonmentioning
confidence: 87%
“…There was a 2.56-fold increase after 10 km and a 4.96-fold increase after 100 km. When normalized to creatinine, these increases were 1.39-and 1.95-fold, respectively [45].…”
Section: Urinary Cystatin C (Ucyst-c)mentioning
confidence: 95%
See 2 more Smart Citations
“…Acute kidney injury (AKI) is described as a relatively common complication of exercise, namely prolonged runs. Wolyniec et al [2] found that typical urinary AKI markers were elevated after both 10 and 100 km runs, and concluded that there seems to be a physiological reaction rather than proof of kidney injury. However, their results support the use of neutrophil gelatinase-associated lipocalin and cystatin-C as the most valuable novel markers which can help in post-exercise AKI diagnosis.…”
Section: Health Biomarkers In Extreme Exercisementioning
confidence: 99%